2022
DOI: 10.3389/fnagi.2021.819373
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Leucine-Rich Repeat Kinase 2 Expression Is Increased and Associated With Disease Severity in Patients With Parkinson’s Disease

Abstract: BackgroundMutations in leucine-rich repeat kinase 2 (LRRK2) comprise a common genetic risk factor for Parkinson’s disease (PD) and inflammatory bowel disease (IBD). We investigated the expression of LRRK2 in colonic biopsies obtained from a cohort of PD patients and healthy controls.MethodsA cohort of 51 PD patients and 40 age- and gender-matched controls who have colonic biopsied samples were recruited. Among these participants, 26 individuals (12 PD patients and 14 controls) had a series of colon biopsies. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The two existing studies on gut expression of LRRK2 in (Liao et al, 2021). The percentage of cells immunoreactive for LRRK2, which were located in the lamina propria and therefore likely of immune origin, was higher in PD subjects when compared with controls.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The two existing studies on gut expression of LRRK2 in (Liao et al, 2021). The percentage of cells immunoreactive for LRRK2, which were located in the lamina propria and therefore likely of immune origin, was higher in PD subjects when compared with controls.…”
Section: Discussionmentioning
confidence: 92%
“…Using sigmoid biopsy lysates from 12 patients with PD (all Caucasian with no family history of PD) and 11 age‐matched controls, we showed that both LRRK2 expression and kinase activity were significantly reduced in the colon of patients with PD when compared with controls (de Guilhem de Lataillade et al 2021). In a subsequent study, Liao et al analyzed the expression of LRRK2 by immunohistochemistry in colonic biopsies from 51 patients with PD (3 with LRRK2 R1441H or I2012T mutations, 9 with the PD risk variant G2385R) and 40 controls (Liao et al, 2021). The percentage of cells immunoreactive for LRRK2, which were located in the lamina propria and therefore likely of immune origin, was higher in PD subjects when compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of the gut as an incubator of LRRK2-expressing cells with pathologic potential in PD, as discussed above, is supported by a study in which it was demonstrated that there is increased LRRK2 expression in colonic biopsies from patients with PD compared to age- and gender-matched control [ 63 ]. In this study, the colonic LRRK2 level in PD patients correlated with disease severity in both motor and cognitive function and the expression levels were higher in those carrying LRRK2 risk or pathogenic polymorphisms rather than wild type LRRK2 polymorphisms.…”
Section: Mucosal Immunological Markers In Pdmentioning
confidence: 94%
“…Most of the pathogenic LRRK2 mutations relating to PD result in hyperactivated kinase activity of LRRK2 protein, and patients carrying the mutation have higher concentrations of pro-inflammatory cytokines in their peripheral circulation [ 175 , 188 , 189 ]. In addition, histopathological studies have demonstrated that LRRK2 expression is up-regulated in colonic biopsy tissue from patients with PD or IBD compared to controls and the expression correlates with disease severity [ 190 192 ]. Thus, exaggerated inflammatory responses attributed to pathogenic LRRK2 mutation upon immune triggers from the gastrointestinal tract contribute to the pathogenesis of PD.…”
Section: Interplay Between Genetic Predisposition and Gut Microenviro...mentioning
confidence: 99%